Swim, fish! : explore the coral reef - Neuman, Susan B. (Washington, D.C. : National Geographic, 2014)
Introduces coral reefs and the animals that live there to young readers using simple, repetitive text and photographs, including seahorses, turtles, eels, and minnows.
Keywords: Coral reef animals -- Juvenile literature; Coral reefs and islands -- Juvenile literature